A Small Molecule TrkB Neurotrophin Receptor Partial Agonist as Possible Treatment for Experimental Nonarteritic Anterior Ischemic Optic Neuropathy. (2nd December 2018) - Ali Shariati, Mohammad; Kumar, Varun; Yang, Tao; Chakraborty, Chandrani; Barres, Ben Anthony; Longo, Frank Michael; Liao, Yaping Joyce
ABSTRACT: Purpose : Brain-derived neurotrophic factor (BDNF) and activation of its high affinity receptor tropomyosin kinase (Trk) B promote retinal ganglion cells (RGCs) survival following injury. In this study, we tested the effects of LM22A-4, a small molecule TrkB receptor-specific partial agonist, on RGC survival in vitro and in experimental nonarteritic anterior ischemic optic neuropathy (AION), the most common acute optic neuropathy in those older than 50 years. Methods : We assessed drug effects on immunopanned, cultured RGCs and calculated RGC survival and assessed TrkB receptor activation by mitogen-activated protein (MAP) kinase translocation. To assess effects in vivo, we induced murine AION and treated the animals with one intravitreal injection and three-week systemic treatment. We measured drug effects using serial spectral-domain optical coherence tomography (OCT) and quantified retinal Brn3A + RGC density three weeks after ischemia. Results : In vitro, LM22A-4 significantly increased the survival of cultured RGCs at day 2 (95% CI control: 8.4–13.6; LM22A-4: 23.7–30.3; BDNF: 24.3–29.9; P ≤ 0.0001), similar to the effect of the endogenous TrkB receptor ligand BDNF. There was also significant nuclear and cytoplasmic translocation of MAP kinase (95% CI control: 0.9–6.8; LM22A-4: 38.8–84.4; BDNF: 64.0–93.0; P = 0.0002), a known downstream event of TrkB receptor activation. Following AION, LM22A-4 treatment led to significant preservation of the ganglion cell complex (95% CI: AION-PBS: 66.8–70.7%; AION-LM22A-4: 70.0–73.1; P = 0.03) and total retinal thickness (95% CI: AION-PBS: 185–196%; AION-LM22A-4: 195–203; P = 0.002) as measured by OCT compared with non-treated eyes. There was also significant rescue of the Brn3A + RGC density on morphometric analysis of whole mount retinae (95% CI control: 2360–2629; AION-PBS: 1647–2008 cells/mm 2 ; AION-LM22A-4: 1958–2216 cells/mm 2 ; P = 0.02). Conclusions : TrkB receptor partial agonist LM22A-4 promoted survival of cultured RGCs in vitro by TrkB receptor activation, and treatment in vivo led to increased survival of RGCs after optic nerve ischemia, providing support that LM22A-4 may be effective therapy to treat ischemic optic neuropathy. Abbreviations : AION: anterior ischemic optic neuropathy, BDNF: Brain-derived neurotrophic factor, GCC: ganglion cell complex, MAP: mitogen-activated protein, OCT: spectral-domain optical coherence tomography, OD: right eye, ON: optic nerve, ONH: optic nerve head, OS: left eye, RGC: retinal ganglion cell; Trk: tropomyosin kinase